Encyclopedia of Inorganic and Bioinorganic Chemistry 2022
DOI: 10.1002/9781119951438.eibc2825
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic Ferrocenyl Complexes and Their Application in the Treatment of Cancer

Abstract: Ferrocene, a stable 18‐electron metallocene, has been readily modified to include other functionalities by reactions such as Friedel–Crafts and Mannich. While ferrocene and its derivatives have many applications, for example, as fuel additives and materials chemistry, they have been heavily researched in the past three decades for their medicinal applications; namely, tamoxifen, a well‐known breast cancer drug, has been modified with ferrocene (ferrocifen) to improve breast cancer selectivity, and chloroquine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…18 Heterobimetallic species have the potential benefit of both metals working together, and by combining ruthenium and ferrocene into a singular complex, it is possible to have synergistic effects against cancer cells. 17,19,20 Alongside other research groups, in 2021, we reported the synthesis of heterobimetallic ruthenium−ferrocenyl complexes, [(bpy) 2 (Fc-acac)Ru][PF 6 ] (bpy = 2,2′-bipyridine; Figure 1F) 21 and highlighted their excellent nanomolar cytotoxicity against both human pancreatic carcinoma (MIA PaCa-2) and human colorectal carcinoma p53-wildtype (HCT116 p53 +/+ ) cell lines with dose-dependent double-strand DNA damage, which is correlated to their cytotoxicity. In 2022, Manikandan et al reported Ru(II) piano-stool complexes of the type [(arene)RuCl(Fc-acac)], where arene = p-cymene (p-cym) or 1,2,3,4,5-pentamethylcyclopentadiene (Cp*) and Fc-acac = a functionalized ferrocenyl β-diketonate ligand with either a methyl or trifluoromethyl group (Figure 1G).…”
Section: ■ Introductionmentioning
confidence: 99%
“…18 Heterobimetallic species have the potential benefit of both metals working together, and by combining ruthenium and ferrocene into a singular complex, it is possible to have synergistic effects against cancer cells. 17,19,20 Alongside other research groups, in 2021, we reported the synthesis of heterobimetallic ruthenium−ferrocenyl complexes, [(bpy) 2 (Fc-acac)Ru][PF 6 ] (bpy = 2,2′-bipyridine; Figure 1F) 21 and highlighted their excellent nanomolar cytotoxicity against both human pancreatic carcinoma (MIA PaCa-2) and human colorectal carcinoma p53-wildtype (HCT116 p53 +/+ ) cell lines with dose-dependent double-strand DNA damage, which is correlated to their cytotoxicity. In 2022, Manikandan et al reported Ru(II) piano-stool complexes of the type [(arene)RuCl(Fc-acac)], where arene = p-cymene (p-cym) or 1,2,3,4,5-pentamethylcyclopentadiene (Cp*) and Fc-acac = a functionalized ferrocenyl β-diketonate ligand with either a methyl or trifluoromethyl group (Figure 1G).…”
Section: ■ Introductionmentioning
confidence: 99%